1978
DOI: 10.1002/cpt1978235553
|View full text |Cite
|
Sign up to set email alerts
|

Trimethoprim/sulfamethoxazole and renal function in transplant patients

Abstract: Twenty-two patients with functioning renal allografts took part in a double-blind crossover trial during which placebo, sulfamethoxazole, and trimethoprim/sulfamethoxazole were given for periods of 14 days. The patients were divided into 2 groups. The first group consisting of 12 patients had serum creatinine levels less than 0.18 mmol/L and the second group of 10 patients had serum creatinine levels between 0.18 mmol/L and 0.35 mmol/L. Renal function at the end of each period was assessed by clearance of inul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…With the usual dose of TMP/SMX, the TMP component inhibits tubular creatinine secretion, leading to a rapid but reversible increase in the SCr level [10][11][12][13][14][15][16] without altering the glomerular filtration rate. 17 The increase in the SCr level causes an apparent decrease in the calculated creatinine clearance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the usual dose of TMP/SMX, the TMP component inhibits tubular creatinine secretion, leading to a rapid but reversible increase in the SCr level [10][11][12][13][14][15][16] without altering the glomerular filtration rate. 17 The increase in the SCr level causes an apparent decrease in the calculated creatinine clearance.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the effect of TMP on SCr in healthy individuals have shown an average increase in the SCr level of 15% to 35%. [10][11][12][13][14][15][16] A study on TMP and its effect in patients with a 2 Clinical Medicine Insights: Arthritis and Musculoskeletal Disorders normal renal function and those with chronic renal failure reported that the SCr level in patients with a normal renal function did not differ substantially from baseline levels, whereas that in patients with chronic renal failure elevated significantly from the baseline level. 12 In a previous study of outcomes in renal transplant recipients on TMP/SMX prophylaxis for 1 year, 38% of all patients suffered a complication necessitating cessation of TMP/SMX.…”
Section: Introductionmentioning
confidence: 99%